A software for monitoring the search performance of a hybrid ant colony optimization algorithm - See, Phan Chiak, author; Wong, Kuan Yew, supervisor, author; IEEE Regional Student Conference on Research and Development (2008 : Johor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL